2009
DOI: 10.1103/physreve.79.067301
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rise of water in hydrophilic nanopores

Abstract: We report on the capillary rise of water in three-dimensional networks of hydrophilic silica pores with 3.5 nm and 5 nm mean radii, respectively (porous Vycor monoliths). We find classical square root of time Lucas-Washburn laws for the imbibition dynamics over the entire capillary rise times of up to 16 h investigated. Provided we assume two preadsorbed strongly bound layers of water molecules resting at the silica walls, which corresponds to a negative velocity slip length of -0.5 nm for water flow in silica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
188
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(212 citation statements)
references
References 56 publications
24
188
0
Order By: Relevance
“…The entirely filled sample (fraction filling f =1.0) has been obtained by melt infiltration, that is capillaritydriven filling of the channels [8,[77][78][79]. To prepare the partially filled samples (0 < f < 1) we imbibed the porous matrix with binary 7CB/cyclohexane solutions of selected concentrations.…”
Section: Experimental a Sample Preparationmentioning
confidence: 99%
“…The entirely filled sample (fraction filling f =1.0) has been obtained by melt infiltration, that is capillaritydriven filling of the channels [8,[77][78][79]. To prepare the partially filled samples (0 < f < 1) we imbibed the porous matrix with binary 7CB/cyclohexane solutions of selected concentrations.…”
Section: Experimental a Sample Preparationmentioning
confidence: 99%
“…The first regime occurs in pores that are about 2 to 20 nm wide and results from "surface water" [water with structure and dynamics distinct from those of bulk liquid water, found within up to three statistical monolayers (~0.9 nm) from hydrophilic surfaces 34,35 ] constituting a nonnegligible part of the pore water 25,27,34 . In this regime, the average behavior of pore water is sometimes represented with a "core-shell" model, on which pore water is conceptually divided into a core of "free" water with bulk-liquid-like properties and a shell of "surface" water with distinct properties 25,27 . The second regime occurs in pores that are narrower than about 2 nm, where the bulk-liquid-like water core is absent 2,34 and surface water is influenced by confinement between two surfaces rather than by interaction with a single surface 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Ice crystals formed in the free pore water in 2.4 nm diameter pores have a smaller lattice constant than those formed in 4.2 nm diameter pores, suggesting that confinement influences the structure of water even in the core region 29 . More recent research has concentrated on revealing the properties of ambient liquid water in silica nanopores including its structure 3,6,31 , vibrational 5 dynamics 4 , diffusivity 2,32 , and viscosity 25 . These studies showed that the first one or two statistical water monolayers on the silica surface are ordered and much less mobile than the rest of the pore water 3,25,37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise confinement volume below which such collective dynamics, and thus proton-charge diffusion, slows down may be system dependent, and may be slightly larger in systems in which (unlike reverse micelles) more than one water monolayer is immobilized by surface binding. 48 In view of the above-discussed relation between protoncharge diffusion and water dynamics, it is interesting to investigate whether a correlation exists between the average reorientation rate of the water molecules in the nanodroplets and the diffusion constant of the proton. We indeed find (Fig.…”
mentioning
confidence: 99%